The cost of price de-linkages between European gas hubs - Petrovich, B (Oxford Institute for Energy Studies, 2015)
The growth of trading activity on Europe’s gas hubs and access to anonymised OTC price data provides the OIES Gas Programme with the opportunity to analyse and draw conclusions on issues of direct relevance to policy makers and market participants. With 2014 data available, the objective of this paper is primarily to explore the extent to which conclusions reached in the Author’s previous papers have changed. As trading volumes and liquidity increase one would expect to see price correlations across market geography improve, and indeed this is the general trend observed in this paper. Of equal interest however are the anomalies to this trend which may be one-off or recurrent in nature. Beatrice identifies such ‘de-linkages’ and with reference to the work of market monitoring groups and using data on infrastructure capacities and flowrates which has recently become more widely available, applies a forensic approach to assessing the prime causes for such episodes – whether due to physical or contractual congestion. With the IGU’s annual price survey data available at a national market level, a measure of the financial impact on consumers of such price de-linkages is also estimated, helping to focus the minds of policy makers on appropriate actions to ensure the free flow of gas across interconnection points. As the future pattern of gas flows inevitably changes over time, due to LNG import level fluctuations, pipeline import patterns changing and a more diverse supply pattern from the European core to eastern Europe and indeed Ukraine, we should expect this to be a continuing and dynamic challenge.